O crescimento do mercado de academias no Rio Grande do Sul durante a pandemia do COVID-19 - (:unkn) unknown (Universidade Federal do Pampa, 2021)
It is known that the practice of physical exercise is very important for the population's health. However, such practices underwent major transformations during the Covid 19 pandemic. Thus, this work has as a general objective to evaluate the innovation of the fitness market after the beginning of the Covid-19 pandemic. Therefore, some specific objectives will be necessary, such as, for example, analyzing the growth of the fitness market, in particular, gyms in Brazil; assess the perception of practitioners of physical activities regarding new exercise practices; and, recognize changes and innovations in physical exercise practices. Brazil ranks second among the countries that have the largest number of training units, losing only to the United States. During the work, it will be possible to notice changes in the scenario of gyms, in their physical spaces and in the preferences of their regular users and their new customers. It can be seen that the main changes will be related to the spaces where activities are carried out, in which we can highlight the growing demand for open spaces or personalized spaces, such as studios.
The growth of the gym market in Rio Grande do Sul during the COVID-19 pandemic
Keywords: Academias; Crescimento; Inovações; Covid-19; Academies; Growth; Innovations; CNPQ::CIENCIAS SOCIAIS APLICADAS